Fungal Infections of the Central Nervous System - Jia, Dan Tong; Thakur, Kiran (Seminars in Neurology, 2019)
Fungal central nervous system infections present in a myriad of clinical manifestation and remain a significant diagnostic challenge. Presenting symptoms, cerebrospinal fluid analysis, conventional fungal serum markers and imaging correlates of disease are seldom sensitive or specific; fungal culture growth or histopathologic analysis are often required for definitive diagnoses but limited by feasibility. Novel diagnostic tools (such as the cryptococcal antigen and next-generation sequencing) have increased diagnostic potency when available but require further studies to define their utility.Invasive fungal infections are an emerging health threat in the setting of increased immunomodulatory treatments, advancements in transplant medicine and increased world-wide travel. Therefore, strong clinical suspicion from epidemiologic clues, clinical progression and presence of CNS dissemination risk factors must be exercised to pursue broad diagnostic workups and rapidly initiate medical and surgical management. This article will describe the epidemiology, clinical presentations, diagnostic approach and therapeutic interventions for fungal infections in the central nervous system.
Keywords: fungal CNS infection; chronic meningitis; brain abscess; histoplasmosis; coccidiomycosis; blastomycosis; cryptococcal meningitis; candida meningitis; invasive fungal rhinosinusitis; aspergillosis; fungal meningitis outbreak